Progress in pattern recognition, image analysis, computer vision, and applications : 24th Iberoamerican Congress, CIARP 2019, Havana, Cuba, October 28-31, 2019, Proceedings /: 24th Iberoamerican Congress, CIARP 2019, Havana, Cuba, October 28-31, 2019, Proceedings. (2019) - Unknown
No abstract available